Dynamometry in 12 and 13 year old Children: Reference values and association with their Adipose Tissue (Revista horizonte, 2022)
Objective: The objective of the present study was to determine the relationship between adipose tissue and muscular strength in students of 12 and 13 years of age in a municipal school in Llanquihue. Material and Methods: The study was of a comparative descriptive type. 64 students participated, selected by a probabilistic method. The prehensile strength was determined by a standardized protocol using a hand dynamometer, and adipose tissue through electrical bioimpedance. Results: Force differences were found when comparing between sexes, not being significant. According to age, significant differences were observed (p = 0.020), only in the right hand. An inverse correlation was obtained between grip strength and adipose tissue in both hands in men and women. When analyzed by sex, there was an inverse correlation between grip strength and adipose tissue in both hands only among men. While in women the ratio was low (0.286) and moderate (0.353) in the left and right hand respectively. Conclusion: The findings of this research confirm that at an older age, prehensile strength is greater. Only a positive correlation is obtained in both hands only in women.